Science Literacy Improvement Through Game-Based Media for Eighth Grade Students - Arifianti, Aprillia Dwi; Mulyati, Yayuk; Hamimi, Erti; Fardhani, Indra (Universitas Tidar, 2025)
Science education in Indonesia faces challenges in improving students’ science literacy skills, which are often still low. The objectives of this study are to assess the impact of using the “ELGASE” learning media on improving students' science literacy skills and to identify differences in science literacy skills before and after the implementation of the “ELGASE” media. The method in this study was pre-experimental involving 22 students of class VIII. Data were obtained through observation, testing, and documentation collection methods, then analyzed using the normality test and the N-Gain test to evaluate changes in scores. The results showed that the use of “ELGASE” media provided a significant increase in students’ science literacy skills. This improvement is measured through a nonparametric test (Wilcoxon), which indicates the difference or comparison of pretest and posttest scores on each indicator. The study results indicate that the use of “ELGASE” media significantly improved students’ science literacy skills, with the N-Gain score for the first indicator being 0.80 (80%) and for the third indicator 0.92 (92%), classified as “Effective” and “Highly Effective”, respectively. Additionally, the second indicator showed an increase of 0.58 (58%), falling into the “Moderate” category, which demonstrates a medium level of effectiveness in enhancing students’ understanding of the taught material. The conclusion of this research is that the “ELGASE” media is proven effective in improving students’ science literacy skills and can be recommended for use in science learning.